2010
DOI: 10.4161/cbt.10.12.13432
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin 1 is a potential biomarker for radioresistance in head and neck squamous cell carcinoma

Abstract: Radiotherapy remains the backbone of head and neck cancer therapy but response is sometimes impeded by tumor radioresistance. Identifying predictive biomarkers of radiotherapy response is a crucial step towards personalized therapy. The aim of this study was to explore gene expression data in search of biomarkers predictive of the response to radiotherapy in head and neck squamous cell carcinoma (HNSCC). Microarray analysis was performed on five cell lines with various intrinsic radiosensitivity, selected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 39 publications
(45 reference statements)
3
52
0
Order By: Relevance
“…Decreased sensitivity to treatment with cetuximab, cisplatin, and radiation in hypoxic UT-SCC-2 and UT-SCC-14 cells has been attributed to gain of a mesenchymal phenotype. These findings are supported by a study of Holz et al (131) that also showed decreased radiosensitivity in HNSCC cells with a mesenchymal phenotype, and is in agreement with our previous findings that the mesenchymal marker FN1 is upregulated in radioresistant cells (50).…”
Section: The Impact Of Hypoxia On Hnscc Cell Linessupporting
confidence: 82%
“…Decreased sensitivity to treatment with cetuximab, cisplatin, and radiation in hypoxic UT-SCC-2 and UT-SCC-14 cells has been attributed to gain of a mesenchymal phenotype. These findings are supported by a study of Holz et al (131) that also showed decreased radiosensitivity in HNSCC cells with a mesenchymal phenotype, and is in agreement with our previous findings that the mesenchymal marker FN1 is upregulated in radioresistant cells (50).…”
Section: The Impact Of Hypoxia On Hnscc Cell Linessupporting
confidence: 82%
“…Fibronectin is also a candidate biomarker for several solid tumor types, including ovarian, prostate and breast cancer (1,2). In addition to its implication in cancer development, fibronectin also acts as a potential biomarker for treatment-associated resistance (5).…”
Section: Introductionmentioning
confidence: 99%
“…Altered expression of fibronectin, degradation and organization have been associated with a number of pathologies, including cancer (1)(2)(3)(4)(5)(6)(7)(8). Several of the morphological changes observed in tumor types and tumor-derived cell lines have been attributed to decreased expression of fibronectin, increased fibronectin degradation, and/or decreased expression of fibronectin-binding receptors, including α5β1 integrins (1)(2)(3)(4)(5)(6)(7)(8). Fibronectin is also a candidate biomarker for several solid tumor types, including ovarian, prostate and breast cancer (1,2).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations